Imaging biomarker associated with early neurological deterioration in isolated pontine infarction - Song, Xiaowei; He, Feifei; Hou, Duoduo; Zhao, Hongliang; Wei, Chenming; Chen, Le; Pengmao, Zhuoma; Wu, Jian (Frontiers in Neurology, 2024)
ObjectiveTo investigate the association between cerebral small vessel disease burden, along with its individual imaging features, as well as other imaging features and early neurological deterioration in isolated pontine infarction.Methods107 patients with acute isolated pontine infarcts, within 24 h of symptom onset, were retrospectively analyzed. The mean age of the participants was 67 years. The burden of cerebral small vessel disease on brain MRI was assessed, including white matter hyperintensities (WMH), lacunes, cerebral microbleeds (CMB), and enlarged perivascular spaces (EPVS) for each patient. Additionally, other imaging biomarkers including basilar artery plaque features on high-resolution MR vessel wall imaging and intracranial artery stenosis were evaluated simutaneously. END was defined as an increase of ≥1 point on the motor component of the National Institutes of Health Stroke Scale (NIHSS) or an increase of ≥2 points on the total NIHSS score within 72 h of admission. Statistical analyses were performed using t-tests, chi-square tests, and logistic regression.Results33.6% (36/107) of the patients experienced END. The END group exhibited a higher prevalence of hyperlipidemia compared to the non-END group (66.7% vs. 43.7%, p = 0.024). Over 50% of the mechanisms of infarction can be attributed to basilar artery branch disease in both groups, with 58.3% in the END group and 50.7% in the non-END group. In a multivariate regression analysis, neither the total burden of cerebral small vessel disease nor the presence of WMH, CMB, lacunes, or EPVS were significantly associated with END (all p > 0.05). However, basilar artery intraplaque hemorrhage observed on vessel wall imaging was independently associated with END (OR = 3.233, 95% CI 1.032–10.123, p = 0.044).ConclusionNo association was found between the imaging features of cerebral small vessel disease and END in patients with isolated pontine infarction. However, basilar artery intraplaque hemorrhage serve as an independent predictor of END in this population.